Pelatihan Google-Form Sebagai Media Pendaftaran Anggota Bagi Jaringan Pemuda dan Remaja Masjid Indonesia (JPRMI) - Pudjiarti, Eni; Faizah, Siti; Sofica, Verra; Harafani, Hani (Journal Of Computer Science Contributions (JUCOSCO), 2022)
The Covid pandemic has had a major impact on the way people live. This includes community activities. In the era of the pandemic, activities that were initially carried out face-to-face must be limited online. The internet is a solution to avoid direct contact. Activities carried out face to face are assisted by the use of information technology. This service activity aims to improve the skills of the Indonesian Mosque Youth and Youth Network community in utilizing information technology to facilitate work, recording, reporting, and maintaining the health of both community administrators and other community members. The low ability to utilize the Google Form application is a separate obstacle, so that there are still many public services that use manual recording and are not well documented and there is no routine reporting as monitoring and evaluation material. The implementation method consists of six stages, including the partner determination stage, the problem determination stage, the data collection stage, the implementation stage, the monitoring and evaluation stage, and the reporting stage. The form of activity carried out is to provide education about the basic use of Google Forms by holding workshops on community service activities so that participants consisting of administrators who will process data will be more familiar with the use of the Google Form Application to help process data so that it is neater and easier to understand. This activity resulted in the JPRMI community being better prepared to face technological challenges during the pandemic, as well as providing provisions in improving JPRMI community services. In conclusion, JPRMI community officers are able to practice well in making Google Forms that can be used during member registration without using paper/manual recording.